2020
DOI: 10.1021/jacs.0c07249
|View full text |Cite
|
Sign up to set email alerts
|

Edge-Functionalized Polyphthalocyanine Networks with High Oxygen Reduction Reaction Activity

Abstract: Two-dimensional (2D) conjugated aromatic networks (CAN) have been fabricated by ball milling of polymeric cobalt phthalocyanine precursors edge-functionalized with different aromatic acid anhydride substituents. The optimal CAN, obtained by using tetraphenylphthalic anhydride, consists of uniform and thin (2.9 nm) layers with a high BET surface (92 m2 g–1), resulting in well-defined Co–N4 active sites with a high degree of exposure. Thence, this material exhibits excellent electrocatalytic oxygen reduction rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 37 publications
1
61
0
Order By: Relevance
“…[34,35] Notably, in N 1s and Co 2p XPS spectra (Figure S9, Supporting Information) of Co-TMPyP/CCG and Co-TMPyP/G, the peak positions of CoN were blue-shifted, suggesting that more electrons transferred from the porphyrin macrocycle to the central metal ion in Co-TMPyP/CCG and thus resulted in a higher charge density in the catalytically active center. [36] Figure 2b showed the X-ray absorption near-edge structure (XANES) spectra of Co-TMPyP/CCG, Co-TMPyP/G, Co foil, and CoO. The XANES spectra of Co K-edge in Co-TMPyP/CCG exhibited that the absorption edge was located between CoO and Co-TMPyP/G, indicating that the valence of Co was reduced in Co-TMPyP/CCG.…”
Section: Resultsmentioning
confidence: 99%
“…[34,35] Notably, in N 1s and Co 2p XPS spectra (Figure S9, Supporting Information) of Co-TMPyP/CCG and Co-TMPyP/G, the peak positions of CoN were blue-shifted, suggesting that more electrons transferred from the porphyrin macrocycle to the central metal ion in Co-TMPyP/CCG and thus resulted in a higher charge density in the catalytically active center. [36] Figure 2b showed the X-ray absorption near-edge structure (XANES) spectra of Co-TMPyP/CCG, Co-TMPyP/G, Co foil, and CoO. The XANES spectra of Co K-edge in Co-TMPyP/CCG exhibited that the absorption edge was located between CoO and Co-TMPyP/G, indicating that the valence of Co was reduced in Co-TMPyP/CCG.…”
Section: Resultsmentioning
confidence: 99%
“…2 ) confirmed that four structures have been successfully synthesized, where C = N links connecting building blocks were smoothly arranged in corresponding networks, which was also favored by stretch vibration peaks of C = N covalent bonds at ~1600 cm −1 in Fourier transform infrared spectroscopy (FT-IR spectra, Supplementary Fig. 3 ) 47 , 48 . More detailed characterization can be found in the Supplementary Materials.…”
Section: Resultsmentioning
confidence: 64%
“…1 , SEM images shown in Supplementary Fig. 1 ) 46 , 47 . The 13 C solid-state nuclear magnetic resonance (NMR) spectra (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, Fe ions and Mo ions were coordinated with the amino groups of iminoisoindoline monomer and subsequently form phthalocyanine network polymer containing Fe(Mo)N 4 . [ 41 , 42 , 43 ] The proper diameter of the ring cavity in the polyphthalocyanine structure can accommodate Fe and Mo metal atoms, forming a metal phthalocyanine coordination polymer with homogeneous distributions of Fe and Mo. The control samples FePPc and MoPPc were prepared in parallel excepting for using Fe or Mo source alone instead of both for FeMoPPc.…”
Section: Resultsmentioning
confidence: 99%